??? ?????? ?????? ?????? ?????????? ??????? EBU'–MUIN EN-NESEFI VE KELAMI ISTIDLAL METODU - İSMAEL, HİSHAM MUSTAFA (Fırat Üniveristesi, 2022)
Kelam ilmi, inançla ilgili ilkelerin sıhhat ve doğruluğunun araştırıldığı bir ilimdir. Bu ilim, İslam dini etrafında ortaya atılan şüpheleri bertaraf etmek için akli, nakli delil ve burhanları ortaya koymak amacıyla Kur'ân-ı Kerim ve sahih nebevi sünnet içerisinde sabit, kesin deliller yardımıyla İslam inanç esaslarını tespit etmeye yarayan bir ilimdir. Kelam ilmi Allah katında en şerefli ve en üstün, şer'î ve Arap dili ile ilgili kaidelerin sınırlarını belirleme hususunda en kamil anlayışı sağlayan ilimlerden biri olarak kabul edilir. Kelam ilmi, gerçek İslami inanç esaslarını, onları savunmak, şüphe ve bid'at ehlinin görüşlerini çürütmek amacıyla araştırmaya önem verir. Bunu yaparken olgusal gerçekliği ortaya çıkarıp sağlamlaştırmak adına akli, nakli burhan ve delillere dayalı olarak Kelami tartışma metotlarını kullanır. Ebu'l-Mu'în en-Nesefî, Ebû Mansur el-Mâturîdî ekolüne mensup, onun tartışma metotlarını takip eden ve hak sözü yüceltme hususunda onun tarzını benimseyen otoritelerden biri kabul edilir. O, isyankar kulların şüphe ve sapkınlıklarını, ehl-i sünnete muhalif olan Mu'tezile ve diğer mezheplerin itirazlarını akli ve nakli delillerle çürütmüştür. Kendi inancını savunurken de Kur'ân ayetlerinden, nebevi hadislerden, sahabe sözleri ve müctehid alimlerin sözlerinden deliller sunmuştur. Gerçekte Ebu'l-Mu'în en-Nesefî'nin metodolojisi, kelam ilmi çerçevesinde inanç esaslarını tespit etme usulündedir. Bu araştırma, İslam inanç esaslarını ve Nesefî'nin takip ettiği istidlal metodolojisini ele almaktadır. Ayrıca araşırma, söz konusu alimin hayatı ve ilmi kişiliği, Kelam ilmindeki istidlal metodolojisi, bu metodolojiyi kullanırken takip ettiği yöntem ve yolların sınırlarını ve son olarak onun önemli kelami görüşlerini incelemektedir. Çalışma Ebu'l-Mu'în en-Nesefî'nin akli ve nakli delilleri ispat ederken akıl ve nakli kullanma metodunu açıklamayı hedeflemektedir. Çalışma Ebu'l-Mu'în en-Nesefî'nin aklın, delil getirme hususunda esas kabul edilen ve kendisiyle delil getirilen bir hüccet olarak otoritesini yücelttiği sonucuna ulaşmaktadır. Ayrıca nakli delillerle çelişmediği sürece, ortaya koyduğu metodolojik esaslar ve kurallara uygun olarak nakli meseleleri aklın ışığında gözden geçirdiği, nakli delillerden de hiçbirisini ihmal etmediği sonucuna ulaşılmıştır.

The science of kalam is a science in which the soundness and accuracy of the principles related to faith are investigated. This science is a science that helps to determine the principles of Islamic belief with the help of fixed and definitive proofs in the Qur'an and authentic prophetic sunnah in order to eliminate the doubts affirmed around the religion of Islam. The science of kalam is considered to be one of the most honorable and superior sciences in the sight of Allah, and one of the sciences that provides the most perfect understanding in determining the limits of the rules related to the Shari'a and the Arabic language. The science of kalam gives importance to researching the real Islamic belief principles in order to defend them and to refute the views of the people of doubt and bid'ah. While doing this, uses kalami argumentation methods based on rational, transplant evidence and evidence in order to reveal and consolidate the factual reality. Abu'l-Mu'în an-Nasafi is considered one of the authorities who belonged to the school of Abu Mansur al-Maturidi, who followed his methods of discussion and adopted his style in fixing the word of truth. He refuted the doubts and perversions of rebellious servants, and the objections of the Mu'tazila and other sects who were against the Ahl as-Sunna, with rational and transmitted evidence. While defending his own belief, he presented evidence from the verses of the Qur'an, prophetic hadiths, the words of the Companions and the words of mujtahid scholars. In fact, Abu'l-Mu'în an-Nasafi 's methodology is in the method of determining the principles of belief within the framework of the science of kalam. This research deals with the principles of Islamic belief and the inference methodology followed by Nasafi. In addition, the research examines the life and scientific personality of the scholar in question, the methodology of inference in the science of kalam, the limits of the methods and ways he followed while using this methodology, and finally his important theological views. The study aims to explain Abu'l-Mu'în an-Nasafi's method of using reason and narration while proving the mental and transmission evidences. While doing that, it aims to eliminate the. Confusion and ambiguity regarding the accusations made against Ebu'l-Mu'în an-Nasafi about putting the mind ahead of transmission, and to reach a definite conclusion on this issue. The study reaches the conclusion that Abu'l-Mu'în an-Nasafi 's mind exalts its authority as a proof that is accepted as the basis for bringing evidence and with which evidence is brought. In addition, it has been concluded that as long as they do not contradict the transmitted evidences, he reviews the transmitted issues in the light of reason in accordance with the methodological principles and rules he has set forth, and does not neglect any of the transmitted evidences.
Abu al-Moein al-Nasfi and his inferential verbal approach
Keywords: Din